Clinical features and gut microbiota alterations in hypertensive individuals with left ventricular hypertrophy - Cai, Liang; Liu, Guo-Qiang; Zeng, Chun-Mei; Xu, Wen-Feng; Jiang, Ri-Na; Chen, Hai-Yan (Frontiers in Microbiology, 2025)
ObjectiveThis study aims to identify potential diagnostic biomarkers for individuals with hypertension and left ventricular hypertrophy (LVH) by characterizing associated clinical features and gut microbiota profiles.MethodsParticipants were classified into three groups: a hypertrophy group (hypertension with LVH, n = 63), a non-hypertrophy group (hypertension without LVH, n = 64), and a control group (healthy participants, n = 33). Clinical parameters were recorded, and fecal samples were analyzed for microbial diversity, abundance, and distribution.ResultsPatients in the hypertrophy group exhibited elevated body mass index (BMI), uric acid, triglycerides, and homocysteine levels, as well as reduced estimated glomerular filtration rate and high-density lipoprotein cholesterol. Structural cardiac changes were more pronounced in this group. Increased BMI and γ-glutamyl transferase levels emerged as independent risk factors for LVH. A significant reduction in Actinobacteria abundance was observed in the hypertrophy group compared to healthy controls. At the genus level, microbial compositions in the non-hypertrophy and control groups were more similar. Blautia was significantly enriched in patients with LVH, while Streptococcus equinus showed increased abundance at the species level (p < 0.05). The area under the receiver operating characteristic curve for gut microbiota markers in distinguishing patients with LVH from healthy controls was 0.839, and 0.796 when differentiating from patients with hypertension but without LVH.ConclusionPatients with hypertension and LVH demonstrated distinct metabolic abnormalities and alterations in gut microbiota composition. These findings reported potential microbial biomarkers and pathways for the prevention and management of hypertension-related target organ damage.